Lobbying, Counterlobbying, and the Structure of Tariff Protection in Poor and Rich Countries - Cadot, Olivier; Melo, Jaime de; Olarreaga, Marcelo (Washington, DC: World Bank, 2014)
A political economy model of protection is used to determine endogenously the intersectoral patterns of protection. Three propositions are derived that are consistent with the stylized patterns of tariff protection in rich and poor countries: Nominal protection rates escalate with the degree of processing, protection is higher on average in poor countries, and rich countries protect agriculture relatively more than they protect manufacturing, whereas poor countries do the reverse. Numerical simulations for archetypal rich and poor economies confirm that the endogenously determined structure of protection is broadly consistent with observed patterns of protection.